Tinea pedis: a clinico mycological study - Priya, Balakrishnan Thenmozhi; Janaki, Chellam (International Journal of Research in Dermatology, 2017)
Background: To study the varied clinical presentations, the predominant etiological agent and incidence of tinea pedis in relation to sex, age group, occupation and aggravating factors among the patients. Also an attempt was made to know if any significant association is there with blood group and the occurrence of tinea pedis. Methods: A study was conducted among 75 patients who attended Mycology clinic in tertiary care hospital. Detailed history was taken along with complete physical examination and local examination. All cases of tinea pedis were first confirmed by KOH examination. Isolation of the agent was done in Modified SDA medium with cycloheximide. Differentiation of the species was done by culturing on corn meal agar. Results: Prevalence of tinea pedis infection was more common among males with male: female ratio of 2.26:1. The 21- 30 years age group was commonly affected by tinea pedis. The distribution of blood groups reflected the general distribution pattern of the population. Culture positivity was recorded in 81.3%. Conclusions: More incidences of bilateral involvement and recurrent episodes were noted among the shoe wearing population than in the non-shoe wearing population. Any patients diagnosed with tinea pedis should be screened for diabetes as implied by the outcome of the study. Infected toe nails may be the site of primary infection and fungal disease can spread to other body areas from these primary sites. Trichophyton rubrum happened to be the chief isolate.